2011
DOI: 10.1371/journal.pone.0023738
|View full text |Cite
|
Sign up to set email alerts
|

Association of Transcription Factor Gene LMX1B with Autism

Abstract: Multiple lines of evidence suggest a serotoninergic dysfunction in autism. The role of LMX1B in the development and maintenance of serotoninergic neurons is well known. In order to examine the role, if any, of LMX1B with autism pathophysiology, a trio-based SNP association study using 252 family samples from the AGRE was performed. Using pair-wise tagging method, 24 SNPs were selected from the HapMap data, based on their location and minor allele frequency. Two SNPs (rs10732392 and rs12336217) showed moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Lower STX1A expression was also observed in the motor cortex of 7 cases (non-significant) (Nakamura et al, 2011). Similarly, the expression of LIM homeodomain transcription factor 1b (LMX1B), that plays a role in both the development and maintenance of serotoninergic neurons in the adult brain (Dolmazon et al, 2011, Song et al, 2011, was found to be significantly reduced in the anterior cingulate gyrus of autism patients (Thanseem et al, 2011). Moreover, Iwata et al (2014) identified Nethylmaleimide-sensitive factor (NSF) as a novel serotonin transporter-binding protein, and on examining mRNA expression of the serotonin transporter (SLC6A4) and NSF found no significant differences in SLC6A4 expression, although NSF expression showed a trend towards a reduction (Iwata et al, 2014).…”
Section: Serotonergic (5-ht) Dysfunctionmentioning
confidence: 90%
“…Lower STX1A expression was also observed in the motor cortex of 7 cases (non-significant) (Nakamura et al, 2011). Similarly, the expression of LIM homeodomain transcription factor 1b (LMX1B), that plays a role in both the development and maintenance of serotoninergic neurons in the adult brain (Dolmazon et al, 2011, Song et al, 2011, was found to be significantly reduced in the anterior cingulate gyrus of autism patients (Thanseem et al, 2011). Moreover, Iwata et al (2014) identified Nethylmaleimide-sensitive factor (NSF) as a novel serotonin transporter-binding protein, and on examining mRNA expression of the serotonin transporter (SLC6A4) and NSF found no significant differences in SLC6A4 expression, although NSF expression showed a trend towards a reduction (Iwata et al, 2014).…”
Section: Serotonergic (5-ht) Dysfunctionmentioning
confidence: 90%
“…The role of LMX1B in autism pathophysiology has also been assessed through genetic polymorphism and postmortem autistic brain analysis. A family trio‐based study found two SNPs in LMX1B locus associated with autism [104]. LMX1B mRNA expression was also found to be significantly lower in the anterior cingulate gyrus region of autism patients compared with controls [104].…”
Section: Lmx1a and Lmx1b In Health And Diseasementioning
confidence: 99%
“…Glaucoma is one of the manifestation of classical NPS, but we are not aware of the report of an association of autism with LMX1B mutation in NPS. An association between autism and common variants in LMX1B has been reported in a small cohort of patients30. It is therefore likely that the finding of autism in our patients may represent effects of other variants in LMX1B and other modifier genes.…”
Section: Discussionmentioning
confidence: 57%